Bioaugmentation of Entomopathogenic Fungi for Sustainable Agriotes Larvae (Wireworms) Management in Maize - Razinger, Jaka; Praprotnik, Eva; Schroers, Hans-Josef (Frontiers in Plant Science, 2020)
Soil microorganisms influence biotic and abiotic stress tolerance of crops. Most interactions between plant symbiotic and non-symbiotic soil microorganisms and plants occur in the rhizosphere and are sustained through plant exudation / rhizodeposition. Bioaugmentation, i.e., the introduction or amplification of certain plant beneficial microbes (e.g., entomopathogenic fungi) into the rhizosphere, could contribute to controlling insect crop pests and replacing chemical, environmentally unfriendly insecticides. Wireworms, the soil-burrowing larval stages of click beetles (Coleoptera: Elateridae), are major pests of crops including maize, wheat and potatoes, worldwide. Alternative strategies for controlling wireworms are needed because several chemical pesticides used successfully in the past are being phased out because of their ecotoxicity. Therefore, virulence to Agriotes lineatus L. wireworms and plant beneficial traits of entomopathogenic fungi were investigated in a series of laboratory experiments. Tested taxa included environmentally retrieved Metarhizium brunneum Petch. (2 strains), M. robertsii Bisch., Rehner&Humber (Hypocreales: Clavicipitaceae), and Beauveria brongniartii (Sacc.) Petch. and commercially formulated B. bassiana (Bals.-Criv.) Vuill. (Cordycipitaceae) and Bacillus thuringiensis Berliner 1915 var. kurstaki. In-house reared larvae were dipped in conidial suspension and maize and wheat seeds were coated with fungal conidia. Metarhizium brunneum strains 1154 and 1868 significantly increased wireworm mortality. Fungi were significantly more often re-isolated from maize than wheat rhizoplanes in laboratory assays. The strains tested were rarely isolated as endophytes. Metarhizium brunneum strain 1154 stimulated wheat growth, while M. robertsii 1880 stimulated maize growth, whereas M. brunneum 1868 and others did not affect root or shoot length or plant biomass significantly in laboratory settings. Metarhizium brunneum strain 1868, re-isolated most often from maize rhizoplane, caused the highest wireworm mortality. It was further evaluated whether M. brunneum 1868 can protect maize varieties FeroXXY, LG 34.90 and Chapalu from wireworm damage and promote plant growth at field conditions. Plants of all three varieties stemming from seeds treated with conidia of M. brunneum 1868 showed significantly less wireworm damage 3 to 4 weeks after sowing (5- to 6-leaf stage) resulting in a significantly higher initial maize stand. However, only in the variety LG 34.90 a significant increase of the maize stand was observed at harvest time.